Students’ Individual Work on Mathematics as a Factor of Effective Preparation of Specialists of Primary Education - Valentyna Stoliar (Pedagogical Discourse, 2015)
The attention in the article is emphasized on the realization of the concept of credit-transfer system of teaching through the important component – students’ individual work. It is found out that it is individual work that remains one of the most important components, forming the professional of modern level. It is made clear that students’ preparation to their future professional activity should not only guarantee them with theoretical knowledge, but it also should develop intellectual potential, logical thinking, encourage to working-out additional and scientific literature. The problems of optimization of students’ individual work have been examined. The methods of individual work organization and their importance for the conception of self-education have been traced. It is recorded that self-education is a necessary component of self-development, which leads to forming mathematical competence. Peculiarities of individual work organization have been determined and the conditions of students’ individual activity effectiveness have been formed. It is offered to solve the problem of improvement of students’ mathematical preparation in complex by three levels of individual activity organization: reproductive, reconstructive and creative. The conclusion is made that taking into account many factors and peculiarities of students’ individual work organization can guarantee them possibility to become competitive specialists, ready for self-improvement and research activity.